Unrolling the Invisible: Socio-Cultural Grounds of Child Mortality in the Slums of Dhaka - Siddika Fariha, Noushin; Rahman, Md Asifur (South Asian Journal of Social Sciences and Humanities, 2024)
According to World Health Organization, there is an 85% decline in the recorded child deaths from 1971 in Bangladesh from 371.3 to 22.6 per 1000 live births. However, the rate of child mortality is still quite significant considering the growing development of Bangladesh. In maximum literatures, the prevalent reasons behind child mortality are portrayed as complete biological phenomena and medical conditions (e.g., asphyxia, prematurity, and low birth weight) for the children under the age of 5 in Bangladesh. This research focused on the reasons behind child mortality beyond the biological and medical conditions while stressing on finding the preventable causes of child mortality, through a systematic method of death study named Social Autopsy. Social autopsy refers to a structured qualitative research tool that aims at identifying social, behavioral, and health systems contributors to child deaths. Using this tool, the research has identified that multiple socio-cultural, structural, and behavioral conditions along with medical conditions for child mortality. The research was done in two of the biggest slum areas of Dhaka city: Hazaribagh and Kamrangir Char. 15 families who lost children under 5 years and 5 health care providers were interviewed with a semi-structured method to draw an inclusive picture of socio-cultural dynamics of child mortality. The data was analyzed manually through thematic analysis and narrative analysis which showed the interconnection of all the broader underlying reasons and a detailed impacts of specific causes of child mortality.